Correlation Between Physical Activity Measured by a Wearable Device and Quality of Life in Older Adults - Si-hyun Kim (Korean Research Society of Physical Therapy, 2021)
Background: Physical activity and quality of life (QOL) influence the health status of older adults. Recently, the use of wearable devices to monitor physical activity has increased. Objects: This study examined the relationship between the amount of physical activity, measured using a wearable device, and QOL among older adults. Methods: In total, 71 older adults (aged ≥ 65 years) were enrolled. The amount of physical activity was measured using a wearable device with a wrist strap, and daily physical activity was classified according to intensity (sedentary, light, moderate, or very active). Self-reported QOL was evaluated using the Short Form 36 (SF-36) questionnaire. Pearson and Spearman correlation analyses were conducted to analyze parametric and non-parametric variables, respectively. The relationship between amount of daily physical activity and SF-36 scores was assessed. Results: The correlation analyses revealed positive correlations between the amount of moderate- intensity and very active physical activity (minutes/day) and SF-36 scores (p < 0.05). Conclusion: Physical activity of at least moderate intensity is associated with better QOL in older adults. Further studies are required to verify the effects of increased physical activity on QOL in older adults.